KORELASI KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR KOGNITIF PADA PEMBELAJARAN GEOGRAFI DI SEKOLAH MENENGAH ATAS - Nurzanah, Nurzanah; Tamubolon, Budiman; Harjanti, Diah Trismi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The main objective of this research is to examine the connection between students' autonomy in geography education and their cognitive learning achievements in class XI IPS at SMA Negeri 7 Pontianak. The research employed a descriptive method, specifically a correlational study, using correlation research techniques. The study encompassed the entire population of 100 students. Data were collected through indirect communication techniques and documentary study methods. Questionnaires and students' daily test scores served as the data collection instruments. The findings indicated that the level of students' autonomy in geography education for class XI Social Sciences at SMA Negeri 7 Pontianak was 66.78%, categorizing it as "Pretty Good." Additionally, the average cognitive learning outcomes of class XI IPS students at SMA Negeri 7 Pontianak, based on their overall daily test scores, were 72.68%. The statistical analysis utilizing SPSS with the Product Moment Correlation method revealed a calculated value of 1.115, compared to the tabulated value of 0.195 at a significance level of 5%. Consequently, based on these findings, Based on the analysis, it can be inferred that a correlation exists between the level of students' autonomy in learning and their cognitive learning outcomes in the field of geography education for class XI IPS at SMA Negeri 7 Pontianak.